Método para identificação de critérios de desempenho para avaliação e monitoramento de soluções de logística urbana - Carvalho, Ricardo Pessoa de (2017)
The freight transport at the same time is crucial for the economy and urban development and is associated with many externalities. In order to promote a sustainable urban environment, the government adopted measures to mitigate the problems related to urban freight transport, however, such solutions are often implemented without proper planning. This fact causes, solutions are adopted without first knowing the origin of the problems and their origins. This paper aims to propose a method to identify criterions for evaluation and monitoring the transport system that make it possible to measure the performance logistics solutions already adopted. The methodology suggests the application of a questionnaire, survey, using a Likert Scale to characterize the relevance of performance criterion and identify the level of difficulty of obtaining information. For analysis, is suggest to use the Pareto Diagram with purpose to individualize the importance of each performance criterion in the perception range. Following was conducted a case study with government officials and experts to validate method. As a result were created two tables to assist in judging the performance criterions. The analyzes indicated great interest of respondents to mitigate the social impacts, particularly urban congestion and we found that the adoption of a few criterions enables to evaluate and monitor logistics solutions.